2007
DOI: 10.1093/europace/eum242
|View full text |Cite
|
Sign up to set email alerts
|

Septal atrial pacing for the prevention of atrial fibrillation

Abstract: Implantation of an atrial-active fixation lead on the atrial septum is safe and feasible. However, this study showed no significant difference between septal pacing and high atrial pacing, using the endpoints of AF duration and number of AF episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Nevertheless, in a larger multicentre, randomized study, the Atrial Septal Pacing Efficacy Clinical trial (ASPECT), 17 septal pacing did not diminish AF frequency or burden in spite of reducing PACs. 14 These results were confirmed by Hakacova et al 18 that did not find a significant difference in the number of AF episodes and the duration of AF between septal vs. high atrial pacing group. Katsivas et al 19 in a randomized controlled study showed that atrial septal pacing does not prevent AF episodes in patients requiring atrial pacing for sinus node dysfunction when AF episodes are not documented in the 3 months before pacing.…”
Section: Bachmann's Bundle Pacingsupporting
confidence: 54%
“…Nevertheless, in a larger multicentre, randomized study, the Atrial Septal Pacing Efficacy Clinical trial (ASPECT), 17 septal pacing did not diminish AF frequency or burden in spite of reducing PACs. 14 These results were confirmed by Hakacova et al 18 that did not find a significant difference in the number of AF episodes and the duration of AF between septal vs. high atrial pacing group. Katsivas et al 19 in a randomized controlled study showed that atrial septal pacing does not prevent AF episodes in patients requiring atrial pacing for sinus node dysfunction when AF episodes are not documented in the 3 months before pacing.…”
Section: Bachmann's Bundle Pacingsupporting
confidence: 54%
“…20-22 IAS-P was shown [4][5][6][7] to have a beneficial effect of reducing AF compared with RAA-P. However, other studies [8][9][10] failed to show such a beneficial effect. IAS-P is a potential treatment to prevent AF but further study should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…A trend toward increased use of active-fixation screw-in leads may be because of the following advantages: rapid implantation; low dislodgement rate; easy extraction; and ability to select any pacing site. [3][4][5][6][7][8][9][10][11][12] Using active-fixation screw-in leads, Bachmann bundle pacing could decrease the dispersion of atrial refractoriness and may lead to reduction in the incidence of atrial fibrillation. 8) If trans venous implantation via persistent left superior vena cava is intended, it is recommended to use active-fixation screw-in leads with a sufficient length so that a loop in the right atrium can be formed with appropriate fixation to the right ventricle.…”
Section: Discussionmentioning
confidence: 99%